Nik Mustapha new UPM V-C - New Straits Times (2005)
Universiti Putra Malaysia (UPM) deputy vice-chancellor (Research and Innovation) Prof Dr Nik Mustapha Raja Abdullah has been appointed UPM vice-chancellor.